Tumor‐Targeted Inhibition of Monocarboxylate Transporter 1 Improves T‐Cell Immunotherapy of Solid Tumors. Issue 4 (19th May 2020) - Huang, Tongyi; Feng, Qiang; Wang, Zhaohui; Li, Wei; Sun, Zhichen; Wilhelm, Jonathan; Huang, Gang; Vo, Tram; Sumer, Baran D.; Gao, Jinming
Abstract: Export of lactic acid from glycolytic cancer cells to the extracellular tumor milieu has been reported to enhance tumor growth and suppress antitumor immunity. In this study, a pH‐activatable nanodrug is reported for tumor‐targeted inhibition of monocarboxylate transporter‐1 (MCT1) that reverses lactic acid‐induced tumor immunosuppression. The nanodrug is composed of an MCT1 inhibitor (AZD3965) loaded inside the ultra‐pH‐sensitive nanoparticles (AZD‐UPS NPs). AZD‐UPS NP is produced by a microfluidics method with improved drug loading efficiency and optimal nanoparticle size over sonication methods. The nanodrug remains as intact micelles at pH 7.4 but rapidly disassembles and releases payload upon exposure to acidic pH. When combined with anti‐PD‐1 therapy, AZD‐UPS NP leads to potent tumor growth inhibition and increases survival in two tumor models over oral administration of AZD3965 at dramatically reduced dose (>200‐fold). Safety evaluations demonstrate reduced drug distribution in heart and liver tissues with decrease in toxic biomarkers such as cardiac troponin by the nanodrug. Increased T‐cell infiltration and reduced exhaustive PD1 + Tim3 + T cells are found in tumors. These data illustrate that tumor‐targeted inhibition of MCT1 can reverse the immune suppressive microenvironment of solid tumors for increased safety and antitumor efficacy of cancer immunotherapy. Abstract : A pH‐activatable nanodrug is established for tumor‐targeted inhibition of MCT1 that reverses lactic acid‐induced immunosuppression in solid tumors. The nanodrug is composed of an MCT1 inhibitor (AZD3965) loaded inside the ultra‐pH‐sensitive nanoparticles (AZD‐UPS NPs), and allows for tumor‐specific inhibition of lactic acid exportation. Combining with anti‐PD‐1, the nanodrug synergistically inhibits tumor growth by enhancing CD8 T cell infiltration with reduced exhaustion inside tumors.